Learning takes time: Biotic resistance by native herbivores increases through the invasion process. (9th October 2022) - Santamaría, Jorge; Golo, Raül; Verdura, Jana; Tomas, Fiona; Ballesteros, Enric; Alcoverro, Teresa; Arthur, Rohan; Cebrian, Emma
Abstract: As invasive species spread, the ability of local communities to resist invasion depends on the strength of biotic interactions. Evolutionarily unused to the invader, native predators or herbivores may be initially wary of consuming newcomers, allowing them to proliferate. However, these relationships may be highly dynamic, and novel consumer–resource interactions could form as familiarity grows. Here, we explore the development of effective biotic resistance towards a highly invasive alga using multiple space‐for‐time approaches. We show that the principal native Mediterranean herbivore learns to consume the invader within less than a decade. At recently invaded sites, the herbivore actively avoided the alga, shifting to distinct preference and high consumptions at older sites. This rapid strengthening of the interaction contributed to the eventual collapse of the alga after an initial dominance. Therefore, our results stress the importance of conserving key native populations to allow communities to develop effective resistance mechanisms against invaders. Abstract : As invasions progress, so does the familiarity of native consumers towards invaders. This leads to an increase in the strength of consumer‐resource interactions and can contribute to the control of invader populations. Interestingly, high sociality within native consumers can increase the transmission of information on palatability, shortening the time needed for the increase in the biotic resistance of the system, from decades to years.